Isomerization of n - pentane over PT and Zn - impregnated HZSM5 catalysts - Nurul Aini Mohamed Razali, 1984-, author; Aishah Abd. Jalil, author; Sugeng Triwahyono, author; Nur Hanis Hayati Hairom, author; Ainul Hakimah Karim, 1985-, author; International Conference on Chemical & Bioprocess Engineering (3rd: 2009: Sabah) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL